Marriage strategies of parishioners of Velike Brusnice beneath Gorjanci near Novo mesto - Rožman, Irena (Two Homelands, 2007)
The essay deals with the relationship between marriage and other survival strategies based on the micro ethnologic-demographic study of the way of life of parishioners of Velike Brusnice (Slovenia), located under the hilly Gorjanci between 1840 and 1945. The research of social and cultural characteristics of a self-sufficient family-farming economy, which determine the marriage rules – why, when, and whom to marry - cannot neglect the parishioners’ mainly economic contacts with the inhabitants of neighbouring Žumberk. The author tries to explain the reasons for their prominent endogamy, which is hypothetically the main reason for not marrying with the people of Žumberk in Croatia. The author explains the endogamic rules by the marriage pattern. In this regard she discusses on the one hand the natural conditions for farming, and on the other, the effects of accelerated growth of the population of Brusnice – their emigration and creation of class differences due to the agrarian overpopulation. The emigration process was closely connected to the limited possibilities for income. The Brusnice parishioners did not balance the essential resources and population growth with marriages only; preventing emigration and dividing estates into smaller units would be unsuccessful during the spurs of population growth. The effects of industrialization enabled the socially weakest classes to get married, as well. This can be explained with the mechanism of the so-called “economic nische”, the interpretational model of Hajnal’s thesis about the ‘European marriage pattern’ in the continental agricultural Europe. By this concept, the author seeks to explain those marriages that deviated from the established rules; among them are rear married couples between people from Podgorje and Žumberk. The latter is also confirmed by the archives of the parish Radatovići (Žumberk region in Croatia), where only 8 marriages were registered between 1843 and 2004 with the locals from Podgorje. Most marriages occurred during the years of accelerated population growth. Yet despite busy economic contacts the locals from both parishes did not get married frequently. Oral tradition leads the author to conclude that the lack of marriages between the locals from Podgorje and Žumberk can be ascribed to other perceived cultural differences, particularly of the ‘collective character’ of both economies. Namely, the informants from Podgorje believed that their economies were not compatible but complimentary, which was not in accordance with their endogamic rules that support the marriages among the people from economically, socially and culturally similarly oriented groups. However, it seems that the endogamic rules of people from Podgorje were also a means of maintaining the ethnic and religious boundaries between the locals. It seems that endogamic rules also support the prejudices against people from Žumberk despite many similarities (hard work on poor land, low quality of life, emigration because of agrarian overpopulation, etc.). And finally, the perceived differences between the ways of life of both locals stem from their perceptions of otherness. In this respect, the study of values related to the selection of marriage partners in the context of family structure and family economy, would be of great importance.